Quality of life and clinical characteristics of self‐improving congenital ichthyosis within the disease spectrum of autosomal‐recessive congenital ichthyosis. (13th January 2022) - Hake, L.; Süßmuth, K.; Komlosi, K.; Kopp, J.; Drerup, C.; Metze, D.; Traupe, H.; Hausser, I.; Eckl, K.M.; Hennies, H.C.; Fischer, J.; Oji, V.
Abstract: Background: Autosomal‐recessive congenital ichthyosis (ARCI) is a heterogeneous group of ichthyoses presenting at birth. Self‐improving congenital ichthyosis (SICI) is a subtype of ARCI and is diagnosed when skin condition improves remarkably (within years) after birth. So far, there are sparse data on SICI and quality of life (QoL) in this ARCI subtype. This study aims to further delineate the clinical spectrum of SICI as a rather unique subtype of ARCI. Objectives: This prospective study included 78 patients (median age: 15 years) with ARCI who were subdivided in SICI ( n  = 18) and non‐SICI patients (nSICI, n  = 60) by their ARCI phenotype. Methods: Quality of life (QoL) was assessed using the (Children's) Dermatology Life Quality Index. Statistical analysis was performed with chi‐squared and t‐Tests . Results: The genetically confirmed SICI patients presented causative mutations in the following genes: ALOXE3 (8/16; 50.0%), ALOX12B (6/16; 37.5%), PNPLA1 (1/16; 6.3%) and CYP4F22 (1/16; 6.3%). Hypo‐/anhidrosis and insufficient vitamin D levels (<30 ng/mL) were often seen in SICI patients. Brachydactyly (a shortening of the 4th and 5th fingers) was statistically more frequent in SICI ( P  = 0.023) than in nSICI patients. A kink of the ear's helix was seen in half of the SICI patients and tends to occur more frequently in patients with ALOX12B mutations ( P  = 0.005). QoL was less impaired in patients under the age of 16, regardless of ARCI type. Conclusions: SICI is an underestimated, milder clinical variant of ARCI including distinct features such as brachydactyly and kinking of the ears. Clinical experts should be aware of these features when seeing neonates with a collodion membrane. SICI patients should be regularly checked for clinical parameters such as hypo‐/anhidrosis or vitamin D levels and monitored for changes in quality of life.